Conducting a rapid health promotion audit in suburban Adelaide, South Australia: Can it contribute to revitalising health promotion?. (12th July 2021) - Roesler, Anna; Musolino, Connie; van Eyk, Helen; Flavel, Joanne; Freeman, Toby; Fisher, Matt; MacDougall, Colin; Baum, Fran
Abstract: Issues addressed: How health promotion is implemented varies and it is often not clear what activities are in place in a region. Understanding the extent of health promotion activities helps planning activities. Methods: This research involved a rapid audit of the types of health promotion activities in a suburban region of South Australia. This analysis was guided by the WHO Ottawa Charter's principles. To better understand population needs and which health promoting activities may help, an epidemiological, demographic and social determinants of health profile of southern Adelaide described disease patterns and health inequities. Results: While there was evidence of a range of health promoting activities, most concerned individual or behavioural services. A key finding was the small number of activities that the state health department and local health system were responsible for. Alongside local government, NGOs provided the bulk of health promotion activities. In addition, there were no overarching health promotion strategies or coordinating bodies to evaluate the activities. The epidemiological, demographic and social determinants of health profile found persistent health and social inequities. Conclusion: This rapid audit of health promotion in a region enabled a quick assessment of the current health promotion situation and provided evidence of gaps and areas where policy change should be advocated. So what?: The key findings distilled from this research were designed to inform policy priorities to shift health promotion in southern Adelaide onto a trajectory consistent with the Ottawa Charter and prevent further focus on individualised behaviour change strategies known as 'lifestyle drift'.